Methylation of C9orf72 expansion reduces RNA foci formation and dipeptide-repeat proteins expression in cells. (26th January 2016) - Bauer, Peter O.
Highlights: Repeat methylation reduces molecular pathology in cellular model of c9FTD/ALS. Novel method for C9orf72 repeat methylation levels quantification. This technique could potentially be used in patients as a bio- and prognostic marker. Abstract: A hexanucleotide repeat expansion in the C9orf72 gene is the most common genetic cause of both frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), together referred to as c9FTD/ALS. It has been suggested that a loss of C9orf72 protein expression, the formation of toxic RNA foci and dipeptide-repeat proteins contribute to C9orf72 -related diseases. Interestingly, it has been shown that trimethylation of histones and methylation of CpG islands near the repeat expansion may play a role in the pathogenesis c9FTD/ALS. Recently, methylation of expanded repeat itself has been reported. To further elucidate the mechanisms underlying these diseases, the influence of epigenetic modification in the repeat expansion on its pathogenic effect was assessed. Here, a reduced formation of toxic RNA foci and dipeptide-repeat proteins upon methylation of the GGGGCC repeat in a cellular model of c9FTD/ALS is shown. Additionally, a novel methylcytosine-capture DNA hybridization immunoassay for semi-quantitative detection of the repeat methylation levels is presented, potentially usable for methylation analysis in patients carrying C9orf72 repeat expansion carriers as a diagnostic tool. Presented results suggest that increased level of pathogenic GGGGCC expansion methylation may be sufficient to alleviate the molecular pathology of the C9orf72 -related diseases.